PERBANDINGAN SISTEM PERPAJAKAN TERHADAP USAHA MIKRO KECIL MENENGAH PADA PT. BERKAT TEKNIK JAYA - Assa, Sintya Clara; Tinangon, Jantje J.; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Economic development of a country , is also caused by a number of micro, small and medium enterprises , as well as existing tax system in Indonesia has undergone some changes , to increase state revenue through tax receipts . This study aims to compare the general taxation system in accordance with the Government Regulation number 46 where applied in July 2013 and began to be paid in August 2013. Object of research is PT Berkat Teknik Jaya is a micro, small and medium enterprises company engaged in agriculture and trade. By taking the information in the form and amount of the income tax returns of the company. Based on calculations, by comparing the amount of tax due in the year 2013 by using each system of taxation, it is known that the amount of tax to be paid in accordance with the general taxation system that is Rp.21.000.000 while using Government Regulation No. 46 then the tax should in the pay of Rp .25.787.000. Based on the calculation and analysis , each system of taxation for micro, small and medium enterprises have advantages and disadvantages , but by terms of the amount of tax to be paid then it is more advantageous for the application in accordance with the general taxation system.